2020
DOI: 10.1002/ps.5773
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the novel pyridine sulfide containing SDH based heterocyclic amide fungicide

Abstract: BACKGROUND: Succinate dehydrogenase (SDH) has been identified as one of the most significant targets for fungicide discovery. To date, 23 commercial SDH inhibitor (SDHI) fungicides have been approved for plant protection since the first launch of carboxin in 1966, and extensively applied to combat destructive plant fungi. RESULTS:In this project, 20 novel pyridine sulfide derivatives containing SDH-based heterocyclic amide fungicide were designed, synthesized, and characterized by proton nuclear magnetic reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 28 publications
1
69
0
Order By: Relevance
“…16 In addition, amide structure is widely used in the discovery of pesticides and medicines because the introduction of an amide group to drug molecules can enhance the interaction with receptors, and many amide compounds exhibit significant insecticidal, herbicidal, fungicidal, anticancer, and other bioactivities. [17][18][19] Fenoxanil, mandipropamid, boscalid and fluxapyroxad, for instance, are efficient fungicides. 16 However, the thioether moiety in drug molecules might decrease the lipophilicity and increase the opportunity for hydrogen bond between drug and target enzyme, which is beneficial to enhance the affinity and improve the bioactivity.…”
Section: Dokla Et Al Prepared N-(3-(1-(4-methylbenzyl)-mentioning
confidence: 99%
“…16 In addition, amide structure is widely used in the discovery of pesticides and medicines because the introduction of an amide group to drug molecules can enhance the interaction with receptors, and many amide compounds exhibit significant insecticidal, herbicidal, fungicidal, anticancer, and other bioactivities. [17][18][19] Fenoxanil, mandipropamid, boscalid and fluxapyroxad, for instance, are efficient fungicides. 16 However, the thioether moiety in drug molecules might decrease the lipophilicity and increase the opportunity for hydrogen bond between drug and target enzyme, which is beneficial to enhance the affinity and improve the bioactivity.…”
Section: Dokla Et Al Prepared N-(3-(1-(4-methylbenzyl)-mentioning
confidence: 99%
“…The structures of compounds [36][37][38][39] In 2020, a series of structurally novel 1,3,4-oxadiazole thioether derivatives (46-48, Figure 10) were designed and synthesized by Shi et al [57] and Song et al [58], and bioassay results showed that compound 46 revealed better activity against G. zeae (61.6%), which was superior to that of Hymexazol, compound 47 displayed the best bioassay against U. viciae-fabae (77%) at 100 μg/mL than those of Streptochlorin and Pimprinine, and compound 48 had an inhibitory rate (99%) at 20 μg/mL against P. dissimile, which was equal to that of Streptochlorin. Hua et al [59] synthesized a series of novel thioether derivatives bearing a pyridine moiety and evaluated for their in vitro fungicidal activities against G. zeae, R. solani, C. circumscissa, P. piricola, A. kikuchiana, B. cinerea, C. capsici, and P. melongenae. Among them, compound 49 (Figure 10) displayed excellent inhibitory rates against R. solani and C. circumscissa, with EC 50 values of 37.66 and 35.30 μg/mL, respectively, which were better than those of Fluopyram.…”
Section: Antifungal Activitymentioning
confidence: 99%
“…(AS). e in vivo fungicidal activity of compounds I-5 and II-4 against Physalospora piricola was performed on apples referring to literature methods [23].…”
Section: Fungicidal Activity Measurementmentioning
confidence: 99%